Phenomenology of Zen - Mickūnas, Algis (Problemos, 2001)
Husserlian phenomenology traces experience to its roots in the living present. The latter is constituted by two mutually exclusive and mutually referring structures: permanence and flux. This essay extricates these structures and their correlations at the level of their mutual constitution as they appear in Zen and its practice. Within the latter context, these structures open what for Zen is emptiness, pointing to a level of experience for whose designation we lack words. For phenomenology this level is prior to active or passive constitution and thematization.